Land–atmosphere feedbacks weaken the risks of precipitation extremes over Australia in a warming climate - Mei-Yu Chang; Zhi-Yan Zuo; Liang Qiao; Kai-Wen Zhang; Bo Liu (Advances in Climate Change Research, 2024)
The importance of land–atmosphere feedbacks on regional precipitation changes has been recently noted. However, how land–atmosphere feedbacks shape daily precipitation distributions, particularly the tails of precipitation distributions associated with extreme events, remains unclear on a regional scale. Herein, using the latest land–atmosphere coupling experiments, this study reveals a consistent weakening effect of land–atmosphere feedbacks on the future increase in precipitation extremes over Australia, revealing the most pronounced reduction (56.8%) for the long-term (2080–2099) projection under the low emission (SSP1-2.6) scenario. This weakening effect holds true for shifts in the extreme tail of precipitation distribution, resulting in a reduced risk of precipitation extremes in a warming climate. Land‒atmosphere feedbacks offset 28%–60% of the occurrence risk for the 99th percentile of daily precipitation, with the largest reduction of 172% when precipitation exceeds the 99.7th percentile in the long-term projection under the high emission (SSP5-8.5) scenario. Considering less water replenishment, these feedbacks may reduce the risk of flooding but potentially expedite droughts, highlighting the role of land–atmosphere feedbacks in extreme event projection and regional climate adaptation.